Auriculoterapia para manejo da ansiedade em pessoas vivendo com HIV: ensaio clínico randomizado - Farias, Odaleia de Oliveira (2023)
The prevalence of anxiety in people living with HIV is substantially higher than that of the general population, yet the condition is often underdiagnosed and undertreated. There is evidence of the benefits of auriculotherapy for managing the disorder, however, there are different protocols and none have been evaluated for anxiety in people with HIV. The aim of this study was to analyze the effectiveness of auriculotherapy protocol in reducing anxiety levels in people living with HIV. A parallel randomized placebo-controlled clinical trial was carried out. People with HIV, aged 18 or over and with moderate or higher anxiety were included in the study. The study was carried out at the Carlos Ribeiro Specialized HIV/AIDS Care Service, an outpatient unit located in Fortaleza, Ceará, Brazil. Participants were allocated to one of two groups, the experimental one, consisting of eight auriculotherapy sessions with seeds, held twice a week, on the Shen Men, Sympathetic, Kidney, Neurasthenia and Anxiety points; or placebo, which included treatment at the same frequency at points considered to have no therapeutic effect for anxiety, Foot, Knee, Hand, Elbow and Shoulder. The main outcome was the difference in anxiety means before and after the intervention. Randomization was implemented in blocks of different sizes using Software R and the sequence generated was stored in opaque envelopes and delivered to the auriculotherapist at the time of the intervention. Participants were blind to group allocation. The study included 66 people, 35 randomized to the experimental group and 31 to the control. The median age of the participants was 35 years old, 52(78.8%) were male, 52(78.8%) black or mixed race, 54(81.8%) recognized themselves as cisgender and 49(74.2%) declared themselves non-heterosexual. The groups were homogeneous for all baseline variables. The mean anxiety in the experimental group ranged from 105.5±19.9 at baseline to 85.5±18.3 after the intervention and in the placebo group it was 102.8±21.6 to 101.5±19. 3. Intergroup analyzes demonstrated a significant reduction in anxiety levels in the intervention group compared to placebo (p=0.002), with a mean difference after the intervention between the groups of 16.1 points, Cohen's d = 0.85 (high effect). Mild side effects, mostly local and transient, were reported by 13(19.7%) participants. In conclusion, auriculotherapy is effective to reduce anxiety levels in people living with HIV. Brazilian Clinical Trials Registry: RBR-2jwy9xf. Funding: Cearense Fundation to Support Scientific and Technological Development – Process Number: NP20-0171- 00059.01.00/20; and National Council for Scientific and Technological Development – Process Number: 409290/2021-1.